AVALIAÇÃO DO POTENCIAL GENOTÓXICO DO GLIFOSATO EM ABELHAS APIS MELLIFERA UTILIZANDO O ENSAIO DO COMETA, HISTOPATOLOGIA E ANÁLISES ENZIMÁTICAS - Polyana Mayume Pereira da Silva (2025)
This study investigates the genotoxic and oxidative stress effects of glyphosate, a widely used herbicide, on Apis mellifera bees. Employing a multidisciplinary approach, the research utilized comet assays to evaluate DNA strand breaks, enzymatic analyses for oxidative stress biomarkers (superoxide dismutase and catalase), and histopathological evaluations to identify structural and cellular alterations in the bees' tissues. The primary aim was to assess the dose-dependent relationship between glyphosate exposure and the observed damage, providing insights into the ecological and economic implications of this herbicide on pollinators. The results indicate significant genotoxicity, with increased DNA fragmentation proportional to glyphosate concentrations. Furthermore, enzymatic analyses revealed heightened oxidative stress, evidenced by altered activities of antioxidant enzymes. Histopathological examinations demonstrated intestinal tissue damage, suggesting compromised digestive and metabolic functions. These findings collectively highlight the herbicide's potential to disrupt key physiological processes in bees, thereby threatening their survival and the essential ecosystem services they provide, such as pollination. The study underscores the critical role of A. mellifera as bioindicators for environmental quality and the urgent need for sustainable agricultural practices. By offering robust scientific evidence, this research aims to support policy formulation that prioritizes pollinator health, biodiversity preservation, and long-term agricultural productivity. The implications extend beyond ecological conservation, addressing global concerns over food security and environmental sustainability. Keywords: Apis mellifera, glyphosate, genotoxicity, oxidative stress, pollination, sustainability.